Penegakan Hukum Dalam Rangka Meningkatkan Keselamatan Lalu Lintas - Yudhi Setiawan (Jatiswara, 2015)
From the accidents and traffic violations data collected by the Traffic Directorate of the Legal Construction Unit of Indonesian Police and from our daily observations, they give a description that traffic safety rate and the rate of public obedience to the traffic law / order is very poor. If there is no strategic measure taken to improve safety rate and improve public obedience tothe law, therefore, it will cause great losses, not only lives and properties, it also cause economic loss. The objectives of this research are to find out how the condition of the recent traffic safety and the rate of public obedience to the law is, to find out what factors influencing the condition of traffic safety and the rate of public obedience to the law are, and to find out what the strategic conception of law enforcement able to improve traffic safety and the of public obedience to the law is.